(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This paper presents the investigation on different substrates that can be used in designing of microstrip monopole antenna such as FR – 4, Arlon 250 ™, Rogers RT / Duroid 5880 ™, Teflon and Rogers RO4350 to operate at 3.6GHz frequency. Main aim of this paper is to propose 4 x 4 Multiple-Input Multiple-Output (MIMO) antenna with coplanar waveguide (CPW) fed technique operating at 3.3 – 3.8GHz for advanced 5G mobile applications. With the help of orthogonal mode arrangement, isolation between MIMO antennas is better than 12dB and achieved radiation efficiency of 97 – 98%. Proposed antenna achieves 550MHz impedance bandwidth at S11< -10dB over operating bandwidth from 3.33 GHz to 3.88 GHz and its peak gain value is 4.90dB. The design is suitable for fifth generation mobile communications exhibited by MIMO antenna performance parameters Envelope correlation coefficient (ECC) < 0.01, diversity gain (DG) 10dB, total active reflection coefficient (TARC) <0.3, Channel capacity loss (CCL) < 0.1bits/Hz and mean effective gain (MEG) is greater than 2.5dB. According to simulation results and MIMO parameters, this proposed antenna met the future 5G applications.